Genetic characterization of natural resistance to ticks and babesiosis in cattle: Implications for safer food production - Marine Vardanyan; Manvel Badalyan; Karine Akopyan; Satenik Kharatyan; Laura Harutyunova; Martin Rukhkyan; Ruzanna Hovhannisyan; Zaruhi Dudukchyan; Ilona Vardanyan; Mikael Mikaelyan; Irena Movsisyan; Hrach Manukyan; et al. (Bioactive Compounds in Health and Disease - Online ISSN 2574-0334 Print ISSN 2769-2426, 2026)
Background: Tick-borne hemoparasitic diseases remain a major limiting factor affecting livestock productivity. They affect animal health, productivity, and the safety of animal-derived products. Excessive use of antiparasitic agents may result in the accumulation of drug residues in animal-derived products, which may compromise food safety. Therefore, discovering genetic basis of the natural resistance in livestock is an important area of agricultural biotechnology. Objective: The aim of this study was to identify genetic structures associated with natural resistance to ticks in cattle and to evaluate their potential application in marker-assisted selection for breeding disease-resistant cattle. Methods: The informativeness of selected SSR markers was assessed using PIC, RP, EMR, and MI indices. QTL mapping and population genetic analyses were performed to identify genetic structures associated with resistance. Results: The selected SSR markers exhibited moderate-to-high polymorphism and high informativeness. TGLA53, SPS115, and ILSTS006 were identified as the most informative markers. QTL mapping identified three genetic structures associated with resistance, of which the most prominent was characterized by multilocus control, high allelic diversity, and a high level of heterozygosity. Conclusion: The results obtained show that the use of multilocus genetic structures of resistance in marker selection may support the development of cattle populations with greater resistance to tick-borne diseases and potentially reduce reliance on chemical interventions, thereby contributing to safer and more sustainable animal-derived food production. Novelty of the Study: This study is distinguished by the integrated application of SSR marker informativeness analysis, QTL mapping, and population genetic analysis to evaluate natural genetic resistance to ticks and bovine babesiosis. The findings provide a scientific basis for marker-assisted breeding strategies aimed at improving livestock health and supporting the sustainable production of safe animal-derived foods. Keywords: bovine babesiosis, tick resistance, quantitative trait loci, SSR markers, marker-assisted selection, food safety.